Airline marketing - Lavelle, Bernard (Henry Stewart Talks, 2009)
Marketing to airlines and passengers, London City Airport service features, Objectives, Strategy, Method, Research, Journey purpose of London City Airport passengers, Where do the passengers originate?, Who do the passengers work for?, Catchment areas, Anticipating market demand, Action